2015
DOI: 10.1007/s00221-015-4223-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention to individual identities modulates face processing

Abstract: The ability of attention to apply in a flexible manner to several types of information at various stages of processing has been studied extensively. However, the susceptibility of these effects to the nature of the idiosyncratic items being attended is less understood. In the current study, we used symbolic cues to orient the attention of participants to the subsequent appearance of the face of a famous person (the former king of Spain) or an unfamiliar face. These were matched in perceptual characteristics. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Additionally, previous research has suggested that the access to self-face representation may be also enhanced automatically (Geng et al, 2012;Ma & Han, 2010) or even when self-recognition is irrelevant to the task (Scott, Luciana, Wewerka, & Nelson, 2005;Sui, Zhu, & Han, 2006). Hence, this effect seems to be task-independent, and it is associated with early and later components, as recently proposed (Humphreys & Sui, 2016;Sui & Humphreys, 2015); in contrast, other faces seems to be more influenced by attentional modulations and thus dependent on task demands (Morgan, Klein, Boehm, Shapiro, & Linden, 2008;Ruz, Aranda, Sarmiento, & Sanabria, 2015).…”
Section: The Temporal Perspective In Selfidentity: the Present Studymentioning
confidence: 83%
“…Additionally, previous research has suggested that the access to self-face representation may be also enhanced automatically (Geng et al, 2012;Ma & Han, 2010) or even when self-recognition is irrelevant to the task (Scott, Luciana, Wewerka, & Nelson, 2005;Sui, Zhu, & Han, 2006). Hence, this effect seems to be task-independent, and it is associated with early and later components, as recently proposed (Humphreys & Sui, 2016;Sui & Humphreys, 2015); in contrast, other faces seems to be more influenced by attentional modulations and thus dependent on task demands (Morgan, Klein, Boehm, Shapiro, & Linden, 2008;Ruz, Aranda, Sarmiento, & Sanabria, 2015).…”
Section: The Temporal Perspective In Selfidentity: the Present Studymentioning
confidence: 83%